Drawbacks of work intensification during the COVID-19 pandemic for procrastination and irritation: work from home as a further risk and social support as a potential buffer? - Bendixen, Lydia; Scheel, T.E. (Frontiers in Organizational Psychology, 2024)
The use of information and communication technologies while working from home during the COVID-19 pandemic may have increased flexibility and compatibility of different life domains, but may have also increased work intensification – which in turn may jeopardize wellbeing and task performance. While work intensification is assumed to relate positively to procrastination as well as irritation, the extent of work from home was expected to strengthen these relationships. Social support may attenuate these moderations. The assumptions were tested in two independent, comparable samples (S1, N = 347; S2, N = 1,066) during two stages of the COVID-19 pandemic (November 2020, 2021). Data were collected via online questionnaires using established scales (preregistered before analyses). Work intensification was significantly positively related to procrastination as well as cognitive and affective irritation in both samples. The extent of work from home strengthened the relationship between work intensification and procrastination (S2), while in S1 this held true only when persons reported not having their own study at home. Social support did not moderate the moderations. By replicating results in two different samples, this study contributes by being the first to examine the relationship between work intensification and procrastination, while further confirming the positive relationship between work intensification and irritation. The extent of work from home seems to pose an additional risk for procrastination. Our research extends the research on remote work by showing the downsides, such as work intensification, which is positively related to irritation and procrastination, which are precursors to impaired wellbeing and task performance. This highlights the different negative outcomes that can result from non-ideal working conditions when working from home during the COVID-19 pandemic. Especially given that the pandemic paved the way for a high prevalence of work from home, future research should investigate beneficial contextual factors to provide the evidence base for the design of healthy and productive working conditions.